2018
DOI: 10.1093/pcp/pcy175
|View full text |Cite
|
Sign up to set email alerts
|

miR172 Regulates both Vegetative and Reproductive Development in the Perennial Woody Plant Jatropha curcas

Abstract: Jatropha curcas is a promising feedstock for biofuel production because its oil is highly suitable for processing bio-jet fuels and biodiesel. However, Jatropha exhibits a long juvenile stage in subtropical areas. miR172, a conserved small non-protein-coding RNA molecule with 21 nucleotides, regulates a wide range of developmental processes. To date, however, no studies have examined the function of miR172 in Jatropha. There are five miR172 precursors encoding two mature miR172s in Jatropha, which are expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…Moreover, the transcript abundances of miR172-targeted AP2 s consistently increased in the transgenic plants. The function of the miR172- AP2 module in both vegetative and reproductive development has been studied in various woody plant species 35 . Taken together, our results suggest that other microRNA-target modules directly or indirectly regulated by miR156- SPL s could also affect poplar morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the transcript abundances of miR172-targeted AP2 s consistently increased in the transgenic plants. The function of the miR172- AP2 module in both vegetative and reproductive development has been studied in various woody plant species 35 . Taken together, our results suggest that other microRNA-target modules directly or indirectly regulated by miR156- SPL s could also affect poplar morphology.…”
Section: Discussionmentioning
confidence: 99%
“…There are ve miR172 family members and miR172b could be negatively regulated by miR156e to in uence the juvenile-adult phase change [31]. In the perennial species Jatropha curcas, only two miR172s have been identi ed [41]. However, ten miR172s and only one miR172 (miR172a) were identi ed among the differentially expressed miRNAs in our libraries.…”
Section: Potential Crucial Mirnas In Vegetative Development and Owerimentioning
confidence: 87%
“…[53] showed that hexuple-null mutant of Arabidopsis euAP2 genes phenocopied constitutively overexpressed miR172 in flowering time. Therefore, results obtained by [72,[75][76][77][78][79], from experiments where miR172 was constitutively overexpressed, are equivalent to the loss of function of entire euAP2 genes in the plant species studied.…”
Section: Briefly On Mir172 Regulation Of Euap2 Genesmentioning
confidence: 88%